Leg stiffness decreases during a run to exhaustion at the speed at VO2max - Hayes, P. R.; Caplan, N. (European Journal of Sport Science, 2014)
Vertical and leg stiffness are related to running speed. In endurance running, the ability to maintain stiffness might be more important than the absolute stiffness magnitude. The purpose of this study was to examine changes in vertical and leg stiffness during an exhaustive. Six sub-elite runners (24.2, s = 4.2 years; 1.81, s = 0.03 m; 73.4, s = 4.4 kg) participated in this study. They performed preliminary tests to determine lactate threshold, lactate turnpoint, VO2max, sVO2max and a series of isokinetic endurance tests. During the run to exhaustion runners were videoed (50 Hz) to determine contact and flight times, from which leg (Kleg) and vertical (Kvert) stiffness were calculated. During the run Kleg showed a significant decrease [P = 0.030, effect size statistics (ES) = 0.74], however, the decrease in Kvert was non-significant and of a small magnitude (P = 0.051, ES = 0.32). The distance covered during the run was correlated with delta Kleg (r = -0.868) but not Delta Kvert (r = 0.684). Delta Kleg was very strongly related to Delta ground contact time (r = -0.937) and Delta step length (r = -0.957). The Delta ground contact time had a near perfect relationship with Delta step length (r = 0.995). Isokinetic measures were not significantly correlated with either Delta Kleg. The ability to maintain a short ground contact time appears to be a key determinant of maintaining performance during a run to exhaustion. Minimising this is important for maintaining Kleg. Kleg was not significantly related to isokinetic measures.